DEMOGRAPHIC TARGETING OF USERS IN MOBILE APPLICATIONS FOR LIVESTOCK DIGITAL MARKETING AMONG SMALLHOLDER CATTLE FARMERS - Triatmojo, Agung; Muzayyanah, Mujtahidah Anggriani Ummul; Syahlani, Suci Paramitasari; Guntoro, Budi (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Several livestock diseases leading to high mortality rates among animals have raised concerns about a potential food crisis in Indonesia. To prevent further spread of these diseases, access to livestock sheds has been restricted. This situation has highlighted the importance of developing alternative marketing channels to facilitate livestock trade. The present study investigates the demographic factors that influence farmers' interest in adopting mobile applications for digital livestock marketing in the Special Region of Yogyakarta. The data for this research was collected from a stratified random sample of 968 respondents across four regions. Prior to the interviews, farmers were provided with an introduction and given the opportunity to experience the mobile applications firsthand. The data analysis employed descriptive statistics, non-parametric analysis, and a logistic regression model. The results indicated a significant (p < 0.05) association between variables such as the farmer's age, educational level, women's decision-making power, farming revenue, cattle ownership, farming experience, and interest in using mobile applications for livestock digital marketing. However, no distinction in adoption interest was observed between farmers who were members of agricultural groups and those who were not. These findings have significant methodological implications, as they require independent interviewing among member farmer groups. This study suggests that developers of mobile applications for livestock digital marketing should consider the lack of digital literacy among farmers as a crucial factor influencing their interest in adopting new technologies. Addressing the digital literacy gap could increase the adoption and effective use of these applications within the farming community.